Geomagnetically induced current analysis and mitigation techniques for Malaysian power system network - Zmnako Mohammed Khurshid Abda, Mr. (2023)
For many decades, Geomagnetically Induced Current (GIC) has posed a significant risk over the electrical power grid infrastructures worldwide. The phenomenon is a ground end manifestation of the Geomagnetic Disturbances (GMDs) and space weather arising from a solar activity, which causes half-cycle saturation, and represents a potential hazard for a stable and safe operation of earthed High Voltage (HV) power transformers. The failure to prevent these saturations at an early stage could cause an overwhelming increase in the reactive power demand of the system, relay misoperation, and major damage to transformers or blackout, ultimately leading to severe economic losses. Previous studies have shown that the impact of GIC is not limited to high and mid-latitude regions, but it can also affect power systems located in lower geographic latitudes. It is noteworthy that no GIC impact study on a 500 kV Malaysian power network has been conducted before. Therefore, this study aims to investigate and predict the impact of GIC on a 500 kV power network in Peninsular Malaysia. A detailed power grid was modelled using the Power System Simulator for Engineering (PSS/E) and Power System Computer-Aided Design (PSCAD) software to calculate the GIC in the network and estimate its impacts on the power transformers. The model was comprised of 54 substations and 138 buses with 500 kV, 275 kV, and 132 kV operating voltages interconnected by transmission circuits. Besides, the model included 132 kV of lower voltage systems to investigate their impacts on the enhanced GIC in the network since they imply a higher resistance value. The entire power network was subjected to different geoelectric field strengths in the 0–180° directions and various grounding resistance (GR) values were applied during the analysis. Based on the results, the PSS/E simulation demonstrated that the most vulnerable substations to GMD events and experienced the most severe GICs were those located in the middle of the Malaysian power network and connected to a longer transmission line. The maximum GIC was recorded at substation 22. In addition, the results of different GR values showed that the flow of GICs in the system decreased when the GRs of the substations were increased. The results also recorded that the addition of the 132 kV network decreased the calculated GICs in most substations due to the inclusion of the additional GIC flow path and currents that were directed into the lower voltage substations. Additionally, the PSS/E analysis determined the most critical locations that were prone to high GICs in the power network model. Thus, GIC mitigation systems, which have been modelled in the PSCAD were connected to the power transformers at these locations. These mitigation systems were tested under different working conditions. It was found that the GIC mitigation systems with 1 Ω and 3180 μF protection mode effectively eliminated the injected GICs and clamped resonance overvoltages below the protection level during the GIC event and under faulty condition. The findings of this research could offer a useful guideline to local power utility, researchers, and transformer developers to predict and mitigate the GIC effects, which in turn will improve the reliability of the power supply to the consumers and reduce great financial loss due to such phenomena.